Autoantibodies at the neuromuscular junction - Link to the central nervous system - Vincent, A (Elsevier, 2014)
Antibodies to different membrane proteins, namely acetylcholine receptor, muscle specific kinase and low density lipoprotein receptor-related protein 4, at the neuromuscular junction are well recognised in myasthenia gravis, although the mechanisms responsible for the muscle distribution and fluctuations in function are still not very clear, and some of the issues are discussed below. In addition, the involvement of antibodies to the potassium channel complex proteins in neuromyotonia, help to lead to a better understanding of immunotherapy-responsive central nervous system diseases.